2016
DOI: 10.1021/acs.iecr.6b00201
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Assisted Synthesis of 5-Hydroxymethylfurfural from Starch in AlCl3·6H2O/DMSO/[BMIM]Cl System

Abstract: A successful protocol has been developed for the microwave assisted conversion of corn starch into 5hydroxymethylfurfural (HMF) utilizing aluminum chloride hexahydrate (AlCl 3 •6H 2 O) and 1-butyl-3-methylimidazolium chloride ([BMIM]Cl) ionic liquid. HMF yield as high as 59.8 wt % was achieved at 150 °C within a short reaction time of 20 min. The dimethyl sulfoxide (DMSO)/[BMIM]Cl system was found to be tolerant to optimal water content which influenced the product distribution. Levulinic acid was detected in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 55 publications
1
28
0
Order By: Relevance
“…The capacity of AlCl 3 for the conversion of carbohydrates and polysaccharides into 5-HMF was studied. Rhagavan and co-workers employed a system involving aluminium chloride (AlCl 3 , 6 H 2 O) as a Lewis acid catalyst to perform the direct conversion of corn starch into 5-HMF [ 57 ]. This transformation was carried out in a commercial ionic liquid [BMIm]Cl.…”
Section: Homogeneous Catalyst In Liquidmentioning
confidence: 99%
“…The capacity of AlCl 3 for the conversion of carbohydrates and polysaccharides into 5-HMF was studied. Rhagavan and co-workers employed a system involving aluminium chloride (AlCl 3 , 6 H 2 O) as a Lewis acid catalyst to perform the direct conversion of corn starch into 5-HMF [ 57 ]. This transformation was carried out in a commercial ionic liquid [BMIm]Cl.…”
Section: Homogeneous Catalyst In Liquidmentioning
confidence: 99%
“…94 The conversion of (24) to diisocyanates (25) was accomplished in two steps using diazides as the intermediates. 92 Derivatives from (23), such as diols (26) 98 and diamines (27) have also been prepared. 99 In addition to the derivatives aforementioned, continuous efforts are being put into upgrading HMF.…”
Section: Bio-based Furans Monomers and Derivativesmentioning
confidence: 99%
“…5‐hydroxymethylfurfural (HMF) is a promising platform chemical owing to its sustainability and functional groups available for further reactions. Due to the importance of HMF, research works have focused on several key aspects: (1) biological properties, such as the metabolism of HMF and toxicological effects; (2) synthesis of HMF including the catalysts used, the feedstocks used, and the solvent systems; (3) derivatives of HMF as biofuels precursors, fine chemicals, monomers for polymers; and (4) industrial production of HMF and its derivatives …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that imidazole ILs can effectively solubilize cellulose, and the highest solubility (25 wt.%) of cellulose was achieved in [C 4 mim]Cl under microwave irradiation. Furthermore, compared with traditional solvents, ILs have many advantages, including excellent thermostability, good solubility and negligible vapor pressure, which make them the most promising solvent for cellulose nowadays.…”
Section: Introductionmentioning
confidence: 99%